The Effect of Nitric Oxide Supplement Intake on the Value of Hematological Examination of Health Workers Exposed to Covid-19 - Didik Dwi Winarno; Abdul Rohim Tualek; Noeroel Widajati; Juliana Jalaludin; Nuh Huda; Raden Khairiyatul Afiyah; ,Firman Suryadi Rahman (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: Examination of the diagnostic covid-19 gold standard with real time reverse polymerase chainreaction (RT-PCR) is still limited, so that the initial hematological examination (leukocytes, lymphocytes,neutrophils, platelets, hemoglobin, and neutrophil lymphocyte ratio (NLR) plays an important role inmonitoring the course of covid-19 disease Macrophages release nitric oxide (NO) to kill parasites NOinhibits migration and adhesion of leucocytes to the endothelium. Metode: The research design used preexperimental with one group pre-post test, the total sample was 80 health workers who were exposed toCovid-19, the independent variable was the provision of NO and the dependent variable was the result ofa hematological examination (leukocytes, lymposites, platelets, neutrophils, hemoglobin and NLR). Theintervention was given NO 500 mg mixed with warm water 250 cc, given 3 times a day for 5 days, dataanalysis used the T-test with a significance value of a<0.05. Results: There is a difference in the resultsof the pre and post-test hematology giving NO to the results of the examination of leucocytes a=0.001,lymphocytes a=0.000, platelets a=0.000, neutrophils a=0.000, hemoglobin a=0.031, and NLR a=0.000.Conclusion: Giving NO to health workers exposed to Covid-19 can improve the hematology and immunesystems to fight the corona virus.